The Principle of Good Faith in Contract Performance: A Civil Law Perspective - Alwi Jaya; Taqiyuddin Kadir; Sudarti (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The principle of good faith constitutes a fundamental doctrine in civil law that governs not only the formation of contracts but also their performance. In contemporary contractual relationships, disputes frequently arise not merely from the violation of explicit contractual terms, but from actions that, while formally compliant, contradict ethical standards, fairness, and reasonable expectations between parties. This condition highlights the growing importance of good faith as a normative benchmark in assessing contractual performance. This study aims to analyze the role and legal significance of the principle of good faith in contract performance from a civil law perspective, particularly in ensuring justice, balance, and legal certainty in private legal relations. This research employs a normative legal research method, relying on a statutory, conceptual, and doctrinal approach. Primary legal materials include civil codes, judicial decisions, and international legal instruments relevant to contract law, while secondary materials consist of scholarly writings, legal commentaries, and academic journals. The analysis is conducted through systematic interpretation and legal reasoning to examine how the principle of good faith operates in contractual performance and dispute resolution. The findings of this study indicate that the principle of good faith functions as an open norm that complements contractual obligations beyond written provisions. It serves as a corrective mechanism against opportunistic behavior, abuse of rights, and rigid contractual interpretation. Furthermore, good faith enables judges to evaluate the fairness of contract performance by considering moral standards, social values, and reasonable expectations of the parties. This research concludes that the principle of good faith is essential for achieving substantive justice in contract law and should be consistently applied to strengthen the integrity and reliability of contractual relationships in civil law systems